"The Returning Echoes of Our Memory": Networks of Memory and Postcolonial Trauma in Tan Twang Eng's The Gift of Rain - Saxena, Vandana (Archīum Ateneo, 2024)
In the societies forged at the anvil of colonial violence, the stories of the past are a contested territory. For postcolonial writers, literature offers a space to explore the trauma that marks the colonial experience and also to forge connections based on common suffering and loss. Stories and experience, when shared, produce new social relations and understanding to replace the relationships and legacies of the past. This paper explores Tan Twan Eng’s novel, The Gift of Rain, to trace the interlinked legacies of the Second World War and colonialism in Malaysia. As Tan’s characters—all from varied cultural and national backgrounds—meet, the cross-cultural storytelling creates a network of memories that transcend the boundaries of nationality, culture, and ethnicity. Trauma acquires a transnational and transhistorical dimension which enables the protagonists to live and engage with the colonial legacy.